2021
DOI: 10.3390/cancers13205036
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Treatment of Relapsed and Refractory Multiple Myeloma in Patients with Renal Insufficiency: Novel Agents, Immunotherapies and Beyond

Abstract: Background: Renal insufficiency is one of the most frequent complications in multiple myeloma. The incidence of renal insufficiency in patients with multiple myeloma ranges from 20% to 50%. Renal impairment in patients with multiple myeloma results primarily from the toxic effects of monoclonal light chains on the kidneys. Dehydration, hypercalcemia, hyperuricemia, the application of nephrotoxic NSARs, antibiotics, contrast agents, etc., all play a major role in the deterioration of renal function in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…5 In addition, subgroup analyses of pivotal clinical trials have shown the efficacy and safety of daratumumaband isatuximab-based combinations in MM patients with moderate RI. 2 The median OS of patients on dialysis was almost half of that for non-dialysis patients (12.5 and 24.5 months, respectively) and the RRR for dialysis-dependent patients was almost five-fold lower than the RRR for dialysis-independent patients. These findings are aligned with earlier reports on the OS of such patients and indicative of the poor prognosis of patients requiring dialysis, at any stage of the disease, whereas independence from dialysis may be associated with improved survival.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…5 In addition, subgroup analyses of pivotal clinical trials have shown the efficacy and safety of daratumumaband isatuximab-based combinations in MM patients with moderate RI. 2 The median OS of patients on dialysis was almost half of that for non-dialysis patients (12.5 and 24.5 months, respectively) and the RRR for dialysis-dependent patients was almost five-fold lower than the RRR for dialysis-independent patients. These findings are aligned with earlier reports on the OS of such patients and indicative of the poor prognosis of patients requiring dialysis, at any stage of the disease, whereas independence from dialysis may be associated with improved survival.…”
mentioning
confidence: 87%
“…Until today there are small case series and case reports showing that daratumumab-based regimens can be safely administered in patients with MM and RI without need for dose modifications. 2 Kuzume et al retrospectively reported the outcomes of 13 MM patients with eGFR ≤15 mL/min/1.73 m 2 who received daratumumab as induction or intensification therapy for patients with suboptimal (less than CR) disease response to upfront therapy. 3 Daratumumab resulted in a rapid reduction of free light chain levels in 10 out of 13 patients, which is important to reverse RI in MM.…”
mentioning
confidence: 99%
“…However, newer-generation ADCs such as belantamab mafodotin have MMAF linkages which do not cleave extracellularly or in plasma, and this appears to have markedly reduced the nephrotoxic potential clinically. 46 Renal pathology was noted in preclinical toxicity studies in animals given belantamab mafodotin at high doses, including tubule degeneration, with characteristic bizarre karyomegalic nuclei related to microtubule disruption by MMAF. 38 In addition, and as noted in the 2020 FDA summary basis of approval for this drug, ADA-related immune complex formation resulted in glomerulonephritis in monkeys, but these changes were considered species-specific immunogenic lesions based on positive immunohistochemical stains for immune complexes.…”
Section: Antibody-drug Conjugatesmentioning
confidence: 99%
“…It thus appears these drugs do not play a significant factor in potentiating kidney effects, and renal adverse events in patients on either drug were considered due to underlying disease factors unrelated to treatment. [46][47][48][49] Because higher MMAF/MMAE systemic exposures often occur in renally compromised patients given belantamab mafodotin/ brentuximab vendotin, extrarenal adverse reactions are more frequent relative to those with normal renal function. 47,49…”
Section: Antibody-drug Conjugatesmentioning
confidence: 99%
“…According to eGFR, it is further divided into mild renal insufficiency (eGFR 60-30 mL/min/1.73 m 2 ), moderate renal insufficiency (eGFR 60-30 mL/min/1.73 m 2 ) and severe renal insufficiency (eGFR < 15 mL/min/1.73 m 2 to dialysis). (Bozic, et al 2021) And then divided into acute damage and chronic damage according to the occurrence time of renal function damage, because the etiology and prognosis of the two groups may be different, which helps to guide further examination and auxiliary diagnosis. It is generally considered to be 2 weeks, but Italian nephrologists believe that the onset time of early intervention can be relaxed to one month.…”
mentioning
confidence: 99%